Effect of water and crude oil on mechanical and thermal properties of epoxy‐clay nanocomposites. Issue 2 (19th September 2013) - Al‐Qadhi, M.; Merah, N.; Gasem, Z.M.; Abu‐Dheir, N.; Aleem, B.J. Abdul
<x xml:space="preserve">Abstract</x> Epoxy‐clay nanocomposites were synthesized by high shear mixing (HSM) technique using diglycidyl ether of bisphenol A (DGEBA) epoxy reinforced by Nanomer I.30E nanoclay. Disordered intercalated with some exfoliated structure were found in the resultant nanocomposites. The fabricated samples were exposed to water and crude oil to investigate the effect of nanoclay addition on diffusivity and amount of liquid uptake. The results showed good improvement in the barrier properties of epoxy as a result of clay addition. The average reduction in diffusivity and maximum water uptake for nanocomposites containing 1% nanoclay were 51% and 8%, respectively. The maximum water uptake was about double the maximum oil ingress for both neat epoxy and nanocomposites. Obvious degradations in thermal and mechanical properties of neat epoxy and nanocomposites were observed as a result of liquid uptake; with less severe impact on nanocomposites. The reduction in glass transition temperature was about 8% for each 1% of water uptake for nanocomposites as compared to 15% for neat epoxy. The tensile strength and the elastic modulus of neat epoxy and nanocomposites were adversely affected by water and oil uptake while the fracture strain was slightly improved; a behavior found to be proportional to the amount of liquid uptake. The diffusion mechanism of water in neat epoxy was well predicted by Fickian model, while that of the nanocomposites was better fitted with Langmuir model. POLYM. COMPOS., 35:318–326, 2014. © 2013 Society of Plastics Engineers